Analytical high frequency GaN HEMT model for noise simulations. (7th November 2017) - Muhea, Wondwosen Eshetu; Yigletu, Fetene Mulugeta; Lazaro, Antonio; Iñiguez, Benjamin
Abstract: A compact high frequency model for AlGaN/GaN HEMT device valid for noise simulations is presented in this paper. The model is developed based on active transmission line approach and linear two port noise theory that makes it applicable for quasi static as well as non-quasi static device operation. The effects of channel length modulation and velocity saturation are discussed. Moreover, the effect of the gate leakage current on the noise performance of the device is investigated. It is shown that there is an apparent increase in noise generated in the device due to the gate current related shot noise. The common noise figures of merit for HFET are calculated and verified with experimental data.